2015
DOI: 10.1007/s11356-015-5142-y
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenicity and androgenicity screening of PCB sulfate monoesters in human breast cancer MCF-7 cells

Abstract: Recent studies identified PCB sulfate esters as a major product of PCB metabolism. Since hydroxy-PCBs (HO-PCBs), the immediate precursors of PCB sulfates and important contributors to PCB toxicity, were shown to have estrogenic activity, we investigated the estrogenicity/androgenicty of a series of PCB sulfate metabolites. We synthesized the five possible structural sulfate monoester metabolites of PCB 3, a congener shown to be biotransformed to sulfates, a sulfate ester of the paint-specific congener PCB 11, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Forc lasses showing increasing trends,all individual homologs within the class were tested and had similar increasing trends ( Figure 5) and comparable doubling times ( Figure S17). [21] Considering regulatory restrictions and controls implemented for the past 1-2 decades,t he detected stable PCB metabolite trends and increasing PFSAs for the past 3d ecades in polar bears are worth further study.T he presence of these substances in blood means they could disrupt normal physiology,a sr elated OH-PCBs, [22] PFSAs [23] and 4-OH-HpCS [17] bind to serum proteins and can thereby disrupt hormone homeostasis.SO 4 -PCBs bind to estrogen and androgen receptors, [24] and the new chlorinated aromatics (Class 3.1-3.4) may be bioactivated to reactive intermediates (e.g. As shown for most classes of substances discovered, the method benefited tremendously from HPLC to separate isomeric homologs or congeners prior to mass spectral characterization.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Forc lasses showing increasing trends,all individual homologs within the class were tested and had similar increasing trends ( Figure 5) and comparable doubling times ( Figure S17). [21] Considering regulatory restrictions and controls implemented for the past 1-2 decades,t he detected stable PCB metabolite trends and increasing PFSAs for the past 3d ecades in polar bears are worth further study.T he presence of these substances in blood means they could disrupt normal physiology,a sr elated OH-PCBs, [22] PFSAs [23] and 4-OH-HpCS [17] bind to serum proteins and can thereby disrupt hormone homeostasis.SO 4 -PCBs bind to estrogen and androgen receptors, [24] and the new chlorinated aromatics (Class 3.1-3.4) may be bioactivated to reactive intermediates (e.g. As shown for most classes of substances discovered, the method benefited tremendously from HPLC to separate isomeric homologs or congeners prior to mass spectral characterization.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thecontamination of top predator polar bears suggests exposure to the same contaminants in the underlying marine foodweb,a nd the mouse study provides evidence that other mammals,i ncluding people,m ay be exposed to the 5novel classes of PCB metabolites.The novel PCB metabolites described here may have been missed in previous studies of serum due to ah istoric reliance on GCbased techniques that require silica gel clean-up steps, derivatization, and use of strong acids or bases for sample preparation. [21] Considering regulatory restrictions and controls implemented for the past 1-2 decades,t he detected stable PCB metabolite trends and increasing PFSAs for the past 3d ecades in polar bears are worth further study.T he presence of these substances in blood means they could disrupt normal physiology,a sr elated OH-PCBs, [22] PFSAs [23] and 4-OH-HpCS [17] bind to serum proteins and can thereby disrupt hormone homeostasis.SO 4 -PCBs bind to estrogen and androgen receptors, [24] and the new chlorinated aromatics (Class 3.1-3.4) may be bioactivated to reactive intermediates (e.g. epoxides), just as PCBs.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…On the other hand, one PCB metabolite (PCB104) exhibits both, AR antagonistic and ER agonist properties ( 315 ). PCBs may also induce estrogenicity indirectly through inhibition of the estrogen sulfotransferase ( 316 ).…”
Section: Polychlorinated Biphenyls (Pcbs)mentioning
confidence: 99%
“…OH-PCBs interfere with the thyroid hormone system and estrogen and androgen sulfotransferases [60][61][62]. OH-PCBs are known to be cytotoxic, suppress thyroid hormone receptor and have estrogenic activity; their sulfation to PCB-sulfates reduced their activity as estrogen receptors [63,64]. There is a correlation between PCB 11, and its metabolite 4-OH-PCB 11, and mitochondrial oxidative stress [52].…”
Section: Toxicity and Effects On Human Healthmentioning
confidence: 99%
“…Research on human breast cancer MCF-7 cells has indicated that high concentrations of 2'-PCB 3, 4'-PCB 3, 4'-PCB 39, and 4'-PCB 53 sulfates resulted in estrogenic effects, and 4'-PCB 3, 3'-PCB 3, 4'-PCB 53, 4-PCB11, and 4-PCB 39 sulfates and the 4'-OH-PCB 3 had androgenic effects [209]. PCB sulfates have also proved to be ligands of human transthyretin and could influence thyroid hormone homeostasis [36].…”
Section: Pcbs and Effects On Steroid Hormonesmentioning
confidence: 99%